2016
DOI: 10.1016/j.exger.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Conservative fluid management prevents age-associated ventilator induced mortality

Abstract: Background Approximately 800 thousand patients require mechanical ventilation in the United States annually with an in-hospital mortality rate of over 30%. The majority of patients requiring mechanical ventilation are over the age of 65 and advanced age is known to increase the severity of ventilator-induced lung injury (VILI) and in-hosptial mortality rates. However, the mechanisms which predispose aging ventilator patients to increased mortality rates are not fully understood. Ventilation with conservative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
(54 reference statements)
2
16
0
Order By: Relevance
“…Several experiments were previously conducted on mice [ 8 – 10 ] in order to evaluate the underlying mechanisms in aging, For example, Jonathan et al [ 9 ] mechanically ventilated mice at 10 ml/kg tidal volume for about 3 minutes prior to initiating mechanical perturbations to investigate respiratory system mechanics and lung morphology across a more complete spectrum of age groups, 2-, 6-, 18-, 24-, and 30-month-old mice. This experiment showed the aging related decrease in respiratory system resistance and increase in lung compliance between 2-month-old and 24-month-old mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experiments were previously conducted on mice [ 8 – 10 ] in order to evaluate the underlying mechanisms in aging, For example, Jonathan et al [ 9 ] mechanically ventilated mice at 10 ml/kg tidal volume for about 3 minutes prior to initiating mechanical perturbations to investigate respiratory system mechanics and lung morphology across a more complete spectrum of age groups, 2-, 6-, 18-, 24-, and 30-month-old mice. This experiment showed the aging related decrease in respiratory system resistance and increase in lung compliance between 2-month-old and 24-month-old mice.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment showed the aging related decrease in respiratory system resistance and increase in lung compliance between 2-month-old and 24-month-old mice. Recently, Herbert et al [ 10 ] mechanically ventilated 2-month-old and 20-month-old male mice and established that older mice had increased lung compliance and were more prone to ventilator-induced edema and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure-Controlled Ventilator-Induced Lung Injury Model: We mechanically ventilated young (2-3 mo) and old (20-25 mo) C57BL/6J wild-type mice using a Scireq FlexiVent computer-driven small-animal ventilator (Montreal, Canada) and previously cited methods (Herbert et al, 2016) with slight modifications. Mice were anesthetized, tracheotomized, and then ventilated for 5 minutes using a low pressure-controlled strategy (peak inspiratory pressure (PIP): 15 cmH20, respiratory rate (RR): 125 breaths/min, positive end-expiratory pressure (PEEP): 3 cmH20).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…Epidemiological studies also suggest that age is a predictive factor in the severity of VILI; however, the exact molecular mechanisms between age and VILI are still unknown (16, 55, 63). In rodent models of VILI, we and others have shown that age increases susceptibility to ventilator-induced edema, injury, and mortality (1, 36). In general, advanced age is also known to promote an increasingly dysregulated innate immune/inflammatory response to injury with an overall shift towards a proinflammatory state that is known as inflammaging (23).…”
Section: Introductionmentioning
confidence: 94%